Major histocompatibility complex (MHC) restriction of foreign transplantation antigens in rats rendered tolerant at birth (The Rockefeller University Press, 1986)
Evidence is presented that MHC restriction of foreign transplantation antigens occurs when tolerance is induced. Whereas PVG and F344 rats rendered tolerant at birth with (DA X PVG)F1 and (DA X F344)F1 hybrid bone marrow cells (BMC), respectively, accept ACI skin grafts, presumably because the foreign transplantation antigens of these third party grafts, which are MHC-compatible with DA, are recognized only in association with the MHC of the hosts, DA rats rendered tolerant with (DA X PVG)F1 or (DA X F344)F1 hybrid BMC usually reject ACI skin. Further support that MHC restriction accompanies the induction of tolerance is provided by the observation that Lewis.1N rats rendered tolerant at birth with athymic (nude) Wag BMC are much more likely to accept BN.B2 (MHC-compatible with Wag) skin grafts, than BN (MHC- compatible with Lewis.1N) grafts.